Relationships between atitude dimensions and the intention to purchase green food products among Malaysian consumers - Rahim, Hairazi; Shamsudin, Mad Nasir; Radam, Alias; Mohamed, Zainal Abidin (Federal Agricultural Marketing Authority, 2011)
The determinant of attitude dimensions is very important in understanding the attitude role as predictor to the intention to purchase green food products. However, as one of the main predictors to the intention behavioural as suggested in the Theory of Reasoned Action (TORA) model, the measurement of attitude dimensions has been identified by many researchers as difficult and hard to determine. Therefore, this paper aims to explore the underlying dimensions that influence consumers' intentional behaviour in purchasing green food products and also the relationships between attitude and intention among Malaysian population. This is conducted using 10 questions on both salient beliefs as well as evaluation of the outcomes and intention of the subject to green food products, measured against a six-point Likert scale. A total of 600 respondents were interviewed via a structured questionnaire where respondents had to rank their agreement and the level of importance of the statements given in the questionnaire to gather information on the attitude dimensions that influence them to purchase green food products. Based on the analyses of the study, these underlying dimensions of attitude are found to have positive relationships with the Malaysian consumers' intention to purchase green food products.